Systematic Literature Review: Planning, Implementation, and Evaluation of Assessment for Learning-Based Feedback In Elementary School Mathematics Learning - Aulia Fitriana Adrian; Ayatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: Mathematics learning at the elementary school level continues to face challenges in feedback management that has not been optimally integrated into the learning process. Although Assessment for Learning (AfL) has positioned feedback as a critical component, in practice its planning, implementation, and evaluation are often carried out separately and inconsistently, resulting in a lack of comprehensive understanding. Method: This study employed a Systematic Literature Review (SLR) methodology guided by the PRISMA framework to ensure a systematic and transparent article selection process. Literature searches were conducted across Google Scholar and Scopus databases spanning 2020–2025 using relevant keywords, progressing through stages of identification (100 articles), screening (60 articles), eligibility (40 articles), and final inclusion of 22 articles subjected to in-depth analysis. Result and Disussions: Findings indicate that feedback planning is increasingly oriented toward diagnostic assessment and varied instruments, yet remains dependent on teacher competence. Feedback implementation demonstrably improves student engagement and learning autonomy, despite constraints related to time and strategy variation. Feedback evaluation shows a positive impact on learning outcomes, though instrument quality and implementation sustainability require further strengthening. Overall, AfL-based feedback management requires more systematic integration to effectively support meaningful and effective mathematics learning.